Survivors : The Broken Path - Book 4 - Hunter, Erin (New York, NY : HarperCollins, 2014)
"Lucky and the rest of his Pack encounter another group of dogs that has survived the Big Growl--and these new dogs may be their most dangerous enemies yet"--
Keywords: Dogs -- Fiction; Wild dogs -- Fiction; Survival -- Fiction; Adventure and adventurers -- Fiction; Fantasy; JUVENILE FICTION / Animals / Dogs; JUVENILE FICTION / Action & Adventure / General; JUVENILE FICTION / Fantasy & Magic